Establishing Economic Empowerment System Through Mosque Based Community - Imari, Iqbal; Mahendra Utama Cahya Ramadhan (Program Studi Ekonomi Syariah, FEBI UIN Datokarama Palu, 2025)
Mosques serve not only as places of worship but also as centers for education, social cohesion, and community welfare. Despite this, their potential role in economic empowerment remains significantly underexplored. Addressing this gap, the study aims to develop a holistic, mosque-based economic empowerment model that aligns with Islamic values and responds to contemporary socioeconomic challenges. The research adopts a qualitative conceptual methodology, synthesizing insights from secondary sources including academic literature and institutional reports on Islamic finance, governance, and community development. The resulting framework is structured around five key stages: community needs assessment, resource mobilization, program development, implementation and monitoring, and long-term sustainability. Findings emphasize the integration of core Islamic principles justice, equity, participation, rewards, and mutual aid (ta’awun) within the broader dimensions of faith (iman), knowledge (‘ilm), and social action (‘amal). The study concludes that mosques can serve as dynamic hubs for inclusive economic growth when empowered with strategic planning and institutional capacity. Its contributions lie in bridging theoretical gaps in mosque-led development models and offering actionable insights for policymakers, mosque administrators, and community stakeholders. The study also highlights the need for future empirical validation to test the model’s adaptability across different cultural and institutional contexts.